Moisture content detection in anchovy sauce using microstrip sensor - Fadhil, Omar Ayad (2014)
Water is the most important parameter to determine the quality of Anchovy Sauce. The changes of m.c in Anchovy Sauce also linked to physicochemical and microbiological changes. Unfortunately to-date, a quick, reliable and accurate method to determine moisture content m.c in Anchovy Sauce has not been reported in the literature. This thesis presents an extensive investigation on the design of a microstrip sensor as a new technique for determination of m.c in Anchovy Sauce in the microwave frequencies from 2 GHz to 3 GHz. The relationships between the dielectric constant as well as loss factor with frequency in Anchovy Sauce has been established. The dielectric constant of the Anchovy Sauce increased almost linearly with increasing m.c. In contrast, the loss factor decreased exponentially with increasing the frequency. The visualization of the electric field distribution of a microstrip loaded with Anchovy Sauce of different percentages of m.c was realized using COMSOL 3.5. It was found that the higher the m.c, the higher will be the detachments of the electric field distribution. The variation of transmission coefficients for different percentages of m.c were measured in the microwave frequencies from 2 to 3 GHz. The results were analyzed and compared to the calculated values using the Finite Element Method (FEM). This is the first work using FEM to evaluate the transmission coefficients of a microstrip sensor loaded with Anchovy Sauce. It was found that the comparison between the calculated and measured magnitude of transmission coefficient of the lowest percentages of m.c exhibit the lowest error and vice versa for the phase of transmission coefficient. The sample with 17.3% of m.c recorded the lowest error of the magnitude of transmission coefficient, while the mean erros of phase of transmission coefficient suggest that the water has the lowest mean error followed by samples with highest percentage of m.c (80.2%). This could be attributed to the inaccurate permittivity model employed by the Agilent Probe. The transmission coefficient of the sensor was found to be highly correlated to the amount of m.c in the Anchovy Sauce for all frequencies except below 2.1 GHz due to the bound water relaxation frequency. Calibration equations to predict the amount of m.c from measured magnitude and phase of transmission coefficient have been established. The calibration equation based on the magnitude of transmission coefficient at 2.55 GHz was found to give the highest accuracy within 1.6% when compared to the actual m.c obtained from the oven drying method.